1981
DOI: 10.2190/uvvy-h0n2-b7v1-mhw0
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase Inhibitors: Prescription and Patient Management

Abstract: The historical roots of the current avoidance of MAOIs are reviewed. A practical approach to the careful prescription of MAOIs is outlined. Medical contraindications, side effects and their management and drug and food interactions with MAOIs are discussed. With careful patient selection, adequate caution by the physican, and appropriate preparation of the patient, MAOIs are often uniquely effective (as in endogenous anxiety) and have an acceptably low potential for serious toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 30 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Since the half-life of phenelzine is 11.6 hours [130] as compared to 0.5–1 hour for hydralazine [131], it might provide additional neuroprotection. Though phenelzine is not a direct vasodilator, as an MAOI it can have a transient effect on blood pressure [132]. Following SCI, when hypotensive effects are particularly undesirable, phenelzine could be used as an alternative to hydralazine.…”
Section: Acrolein As a Novel Therapeutic Target For Spinal Cord Inmentioning
confidence: 99%
“…Since the half-life of phenelzine is 11.6 hours [130] as compared to 0.5–1 hour for hydralazine [131], it might provide additional neuroprotection. Though phenelzine is not a direct vasodilator, as an MAOI it can have a transient effect on blood pressure [132]. Following SCI, when hypotensive effects are particularly undesirable, phenelzine could be used as an alternative to hydralazine.…”
Section: Acrolein As a Novel Therapeutic Target For Spinal Cord Inmentioning
confidence: 99%
“…It is essential that all patients on MAOIs receive dietary and drug precautions (see Tables 1, 2). 9 In our experience, elderly patients comply well and rarely complain about such restrictions. A low tyramine diet is required, necessitating avoidance of foods such as fermented cheese, yogurt, beer, red wine, and excessive amounts of caffeine and chocolate.…”
Section: Precautions and Side Effects Of Maoismentioning
confidence: 66%
“…An unexpected finding was that phenelzine showed a consistent trend to be superior to imipramine. Agoraphobic patients who had been on phenelzine and imipramine at different times during the course of their treatment usually reported that they found phenelzine to be more effective than imipramine (Sheehan et al, 1980b;Sheehan, 1985). Therefore, despite the potential dangers of hypertensive crisis, MAOIs still have clinical application for the treatment of certain types of depression.…”
Section: Discussionmentioning
confidence: 99%